A Compact Soft Robotic Wrist Brace With Origami Actuators - Liu, Sicong; Fang, Zhonggui; Liu, Jianhui; Tang, Kailuan; Luo, Jianwen; Yi, Juan; Hu, Xinyao; Wang, Zheng (Frontiers in Robotics and AI, 2021)
Wrist disability caused by a series of diseases or injuries hinders the patient’s capability to perform activities of daily living (ADL). Rehabilitation devices for the wrist motor function have gained popularity among clinics and researchers due to the convenience of self-rehabilitation. The inherent compliance of soft robots enabled safe human-robot interaction and light-weight characteristics, providing new possibilities to develop wearable devices. Compared with the conventional apparatus, soft robotic wearable rehabilitation devices showed advantages in flexibility, cost and comfort. In this work, a compact and low-profile soft robotic wrist brace was proposed by directly integrating 8 soft origami-patterned actuators on the commercially available wrist brace. The linear motion of the actuators was defined by their origami pattern. The extensions of the actuators were constrained by the brace fabrics, deriving the motions of the wrist joint, i.e. extension/flexion, ulnar/radial deviation. The soft actuators were made of Ethylene-vinyl acetate by blow molding, achieving mass production capability, low cost and high repeatability. The design and fabrication of the soft robotic wrist brace is presented in this work. The experiments on the range of motion, output force, wearing position adaptivity and performance under disturbance, have been carried out with results analyzed. The modular soft actuator approach of design and fabrication of the soft robotic wrist brace has a wide application potential in wearable devices.